2022
DOI: 10.3390/cells11233944
|View full text |Cite
|
Sign up to set email alerts
|

Role of S100A8/A9 in Platelet–Neutrophil Complex Formation during Acute Inflammation

Abstract: Acute respiratory distress syndrome (ARDS) due to pulmonary infections is associated with high morbidity and mortality. Upon inflammation, the alarmin S100A8/A9 is released and stimulates neutrophil recruitment mainly via binding to Toll-like receptor 4 (TLR4). TLR4 is also expressed on platelets, which modulate the immune response through direct interaction with leukocytes. In a murine model of Klebsiella pneumoniae-induced pulmonary inflammation, global S100A9 deficiency resulted in diminished neutrophil rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…22 Mrp 8/14, a protein linked to inflammatory responses, is released abundantly and actively participates in the recruitment of leukocytes and cytokine secretion upon infection, thereby exacerbating inflammatory responses and tissue damage. [23][24][25] In our study, we performed a preliminary experiment exploration and observed a clear detectable difference in the expression level of Mrp 8/14 between septic patients and ARDS patients, which is consistent with the previous study that serum Mrp 8/14 was significantly higher in ARDS and mechanical ventilation patients. 18 However, the higher expression level of Mrp 8/14 observed in our study may be attributed to the inclusion of ARDS patients with not only viral infections but also disease-causing microorganisms such as bacteria compared to the previous one.…”
Section: Discussionsupporting
confidence: 92%
“…22 Mrp 8/14, a protein linked to inflammatory responses, is released abundantly and actively participates in the recruitment of leukocytes and cytokine secretion upon infection, thereby exacerbating inflammatory responses and tissue damage. [23][24][25] In our study, we performed a preliminary experiment exploration and observed a clear detectable difference in the expression level of Mrp 8/14 between septic patients and ARDS patients, which is consistent with the previous study that serum Mrp 8/14 was significantly higher in ARDS and mechanical ventilation patients. 18 However, the higher expression level of Mrp 8/14 observed in our study may be attributed to the inclusion of ARDS patients with not only viral infections but also disease-causing microorganisms such as bacteria compared to the previous one.…”
Section: Discussionsupporting
confidence: 92%
“…A previous study verified that expressions of S100A8/A9 are elevated in blood cells of sepsis patients and S100A8/A9 showed high accuracy in sepsis diagnosis ( 38 ). S100A8/A9 also interacted with platelets under inflammation and regulated neutrophil recruitment ( 39 ). S100A8/A9 bind to TLR-4 and induce platelet pyroptosis, which are highly effective in causing NETosis ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Proteins S100-A8 and S100-A9 present proinflammatory, antimicrobial, oxidant-scaveng ing, and apoptosis-inducing activities. Their proinflammatory activity includes recruitment of leukocytes, promotion of cytokine and chemokine production, and regulation of leukocyte adhesion and migration [33][34][35]. Regarding Heat shock proteins (HSPs), they are associated with the body's metabolic and catabolic processes in addition to immune response and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%